Clinico-microbiological profile and visual outcomes of post-traumatic endophthalmitis at a tertiary eye care center in South India - Vedantham Vasumathy; Nirmalan Praveen; Ramasamy Kim; Prakash Karthik; Namperumalsamy Perumalsamy (Indian Journal of Ophthalmology, 2006)
Purpose: To analyze the clinical and microbiological characteristics of eyes with post-traumatic endophthalmitis and factors influencing the visual outcomes in these cases. Methods: We performed a retrospective chart analysis of the clinical and microbiological data of 97 consecutive patients with post-traumatic endophthalmitis presenting to a tertiary eye care hospital in South India. Results: Thirty-nine (40.2%) cases were culture-positive, Gram-positive cocci (n=24/42, 57.1%) being the commonest isolates. Staphylococcus epidermidis and Pseudomonas aeuruginosa were the commonest single isolates (n=10; 23.8%). Majority of the organisms were sensitive to chloramphenicol (n=27) or ciprofloxacin (n=26). Susceptibility to vancomycin (n=3) and amikacin (n=4) was poor. Cases with negative cultures at presentation were more likely to have improvement in visual acuity compared with culture-positive cases (on multivariate analysis, OR: 3.2, 95% CI: 1.1, 9.0). Conclusions: In this series of post-traumatic endophthalmitis, a high prevalence of resistance of the culture isolates to vancomycin and amikacin was observed.